2009
DOI: 10.1038/jhg.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies ITGA9 conferring risk of nasopharyngeal carcinoma

Abstract: To identify a gene(s) susceptible to nasopharyngeal carcinoma (NPC), we carried out a genome-wide association study (GWAS) through genotyping of more than 500,000 tag single-nucleotide polymorphisms (SNPs), using an initial sample set of 111 unrelated NPC patients and 260 controls of a Malaysian Chinese population. We further evaluated the top 200 SNPs showing the smallest P-values, using a replication sample set that consisted of 168 cases and 252 controls. The combined analysis of the two sets of samples fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 30 publications
(29 reference statements)
3
66
1
Order By: Relevance
“…The results from our phase I cohort confirm and extend previously reported HLA and NPC associations in Southern Chinese populations [22]. Two genome-wide association studies (GWAS) have identified multiple gene association with risk of NPC in Chinese ancestry cohorts [23, 24]. The first GWAS comprised 111 unrelated NPC cases and 260 controls and a replication sample set of 168 cases and 252 controls from the Malaysian Chinese population [23] reported evidence of association with ITGA9 on Chr 3p21.31-21.2.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results from our phase I cohort confirm and extend previously reported HLA and NPC associations in Southern Chinese populations [22]. Two genome-wide association studies (GWAS) have identified multiple gene association with risk of NPC in Chinese ancestry cohorts [23, 24]. The first GWAS comprised 111 unrelated NPC cases and 260 controls and a replication sample set of 168 cases and 252 controls from the Malaysian Chinese population [23] reported evidence of association with ITGA9 on Chr 3p21.31-21.2.…”
Section: Introductionsupporting
confidence: 87%
“…Two genome-wide association studies (GWAS) have identified multiple gene association with risk of NPC in Chinese ancestry cohorts [23, 24]. The first GWAS comprised 111 unrelated NPC cases and 260 controls and a replication sample set of 168 cases and 252 controls from the Malaysian Chinese population [23] reported evidence of association with ITGA9 on Chr 3p21.31-21.2. The second GWAS was conducted in 277 Taiwanese NPC cases and 285 controls and included two independent replication sets.…”
Section: Introductionmentioning
confidence: 99%
“…there must be Austronesian/Tai-Kedai blood ties) and why certain HLA groups are protective while other HLA groups are associated with NPC. Current GWAS studies, which unfortunately specifically exclude the X-chromosome in their analyses, all consistently support the role of the HLA genes, but does not adequately explain the population differences [11][12][13].…”
Section: Nasopharyngeal Cancermentioning
confidence: 95%
“…In particular, α4 and α9 integrin polymorphisms (ITGA4 and ITGA9, respectively) were shown to be associated with autism and nasopharyngeal carcinoma (NPC), respectively. One ITGA4 polymorphism in intron (rs155100) showed association with autism in a Portuguese population, and eight ITGA9 intron polymorphisms (rs169188, rs197721, rs149816, rs169111, rs197770, rs2212020, rs189897, and rs197757 ) were associated with NPC in a Malaysian Chinese population (Correia et al, 2009;Ng et al, 2009). Similar associations between integrin polymorphisms and human diseases in various European populations were proposed by another study, i.e., α4 integrin polymorphisms (ITGA4 ) (rs1449263 in the promoter and rs3770138 in an intron) were significantly associated with multiple sclerosis (MS) in Basque and Nordic populations (The rs1449263 polymorphism was associated with MS only in the Basque population, whereas the rs3770138 was associated only in the Nordic population.)…”
Section: Discussionmentioning
confidence: 99%